Andrographis megamalayana (Andrographinae: Acanthaceae), a new species from the southern Western Ghats, India - Gnanasekaran, Gunadayalan; Karuppusamy, Subbiah; Murthy, Garimella Venkata Suryanarayana (Phytotaxa, 2016)
Andrographis megamalayana Gnanasek., Karupp. & G.V.S. Murthy (Andrographinae: Acanthaceae), a new species from the southern Western Ghats, India, is described here with illustrations, colour photographs, relationships with its allied species and IUCN conservation status. In addition, the pollen and seed morphology have been described here using Light and Scanning Electron Microscopes.